Women students as political activists - Mudau, Elelwani (My University, 2018)
The #FeesMustFall movement introduced a new era of youth uprising in South Africa; it is another example of the many social action movements wherein youth are the driving force and main voice for social change. An interest of this research project was to understand the ways throughout history that social action platforms have been utilized by those involved to assert their values and desires for social change. Social action platforms can be seen as one of the spaces in which humanity asserts its identity. Even during the #FeesMustFall protests in 2015 and 2016, it was evident that a number of identities were being mobilized; the black students’ identities are examples of such and even more was the insertion of black women students during the protests. The heightened role of women students in leadership positions during the protests was explored, especially because women had previously been seen to occupy secondary supporting roles in movements of political change. The project investigated the ways in which these women students inserted their multiple identities that had previously been seen as non-complementary; these identities became a means to address the political agenda of the #FeesMustFall movement. The methodology took a narrative approach to understanding the Experience-Centred narratives told by participants. Application of thematic analysis method produced recurrent narration of events; these particular incident narratives (PINS) (Wengraf, 2006) became important as focal points of analysis. The analysis of participants also revealed the impact of students’ individual upbringing. The family, school and other important influences played key roles in the extent of politicization of participants; from these experiences, leadership qualities were also instilled. Hence during the #FeesMustFall protest, participants were able to engage the movement in the ways they did. Due to their particular background influences, these students were not afraid to lead; neither were they timid about resisting unjust systemic measures on campus or within the movement structures. In the end it was their bodies that curbed police violence on campus.
A research report submitted in partial fulfilment to the degree of Master of Arts in Psychology, Faculty of Humanities, University of the Witwatersrand, 2018
Keywords: Student movements--South Africa; Educational change--South Africa; Universities and colleges--South Africa